Holub József és a Tagányi-könyvtár Pécsre kerülése: Egy „vidéki” történészprofesszori egzisztencia lehetőség-feltételei az 1920-as évek elején (I. közlemény) - Szeberényi, Gábor (Per Aspera ad Astra, 2014)
The position of university professors, who formed a defining group of the intellectual elite between the two world wars, has been the subject of sociological and prosopographical studies. From a biographical point of view, discussions on the subject are mainly limited to the genre of „university memorial literature.” Present study examines historian József Holub’s (1885-1962) appointment as a university teacher and the beginning of his career in Pécs. By reconstructing the actual biographical situation using archival and other sources, the study aims to demonstrate that this significant „prosopographical fact” cannot be judged comprehensively either along the lines of the established schemes of scientific career histories, nor by the later developments of scholarly works and achievements. Furthermore, the study attempts to highlight the methodological and attitudinal limits of the „rationalising” biographical scheme often present at the reconstruction of biographies, and also aims to contribute to the testing of parameters mapped out based on prosopographical/sociological aspects. By achieving the above, it intends to advance the exploration of a more general context using biographical tools: understanding the existential opportunity-conditions of a small town history professor in the 1920’s. The first part of the study discusses József Holub’s work in Budapest, the development of his professional position and relations until spring 1923. (Translated by Ágnes Lengvári)